Pendidikan Literasi Dan Edukasi Politik Untuk Masyarakat Keboansikep Sidoarjo Dalam PILKADA Sidoarjo 2020 - Suyono Suyono; Suhartono Suhartono (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
This study aims to determine the state of political literacy of the Keboansikepl community, as well as to understand the role of the KPU in the context of the state of political literacy. This study uses a qualitative-descriptive approach, to reveal phenomena related to political literacy based on the results of research documents conducted by the Sidoarjo Regency KPU. as well as information from informants from the KPU of East Java Province. The results of the study conclude that the state of political literacy in the Keboansikep community is still very limited only to literacy related to the electoral process and does not reflect education that is oriented towards strengthening the system of understanding and actualizing the rights and obligations of citizens. The new political education is carried out by the KPU through socialization activities, technical guidance (technical guidance) and voter education which it will carry out in the context of the agenda for the stages of the election that will be held as election organizers. The state does not yet have an educational program to improve systemic and sustainable political literacy. The disappointment of the voting community towards the attitude and performance of the leaders and representatives of the people from the general election results in an anomalous phenomenon where the public is known to have knowledge and understanding of politics but it is not consistent with their attitudes and behavior. In political education, the KPU plays a role in conveying information about the election events it holds and providing political education to the public which is only limited to the electoral context for the sake of increasing the percentage of voters turned out and decreasing the percentage of invalid votes